Regulatory Compliance Strengthening Strategy through Mitigating the Risk of Violation of Fiduciary Duty : Jiwasraya Case Study in Indonesia - Senjaya, Pierre; Tarsicius, Tarsicius; Tambunan, Martua E (Journal of Industrial Engineering & Management Research, 2025)
The Jiwasraya case in Indonesia is one of the biggest financial scandals that reflects weaknesses in the implementation of regulatory compliance and internal control, especially related to fiduciary duty violations. This study aims to analyze effective risk mitigation strategies in strengthening regulatory compliance through a case study based on a literature review. By using a qualitative research method through a literature review approach, this study explores various relevant documents, reports, and previous studies. The results of the study indicate that the violation of fiduciary duty in Jiwasraya was caused by weaknesses in investment supervision, lack of transparency in financial reports, and neglect of good corporate governance principles. To address this, the proposed strategies include strengthening internal control mechanisms based on the COSO framework, implementing a whistleblowing system for early detection of violations, and integrating real-time investment monitoring technology. This study provides theoretical contributions by expanding the literature on mitigating the risk of fiduciary duty violations in the context of regulatory compliance. Practically, this study recommends strategic steps for insurance companies and regulators to prevent similar cases from recurring in the future